EFEKTIVITAS MEDIA TARIK GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS PROSEDUR DI KELAS 4 SD - Mustofa, Diva Aghni Aulia; Maulana, Farid Rizqi; Wardana, Deni (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
By recognizing the poor ability of the student to write on the text material of the procedure, the researchers aimed to carry out this research to find out the effectiveness of the image drawing media that is expected to improve the value of the skills of writing the text procedure in students of 4th grade SD based on structural aspects, content, the principle of writing, and skill characteristics. The use of the image drawing learning media is very easy to do because the students are not strangers because the media hamper similar to its use to the games that are often found in front of the school. The media is also easy for teachers to make because they don't use a lot of tools and materials. The approach used in this study is a quantitative approach with one group pre-test post-test method. The population in this study is Class IV SDN Pondok Jagung Timur with a sample of the research class IV B that was taken by random sampling. Data collection techniques are done with pre-test and post-test techniques. Students work on 10 issues of knowledge covering 4 aspects of procedural texts and skills. The results of the study showed that students' skills using drawing media improved based on pre-test and post-test averages. Not only that, based on the test hypothesis paired sample t test also showed a difference between pre-test and post-test. However, on the N Gain Score test the results showed that the influence or improvement occurred was not significant.